Sensation seeking and psychoactive substance consumption: differences between a consumer and a non-consumer sample - González-Gallo, Iván; Rueda-Fernández, Laura Sofía (MedUNAB, 2019)
Introduction. Internationally, there have been several studies carried out in order to demonstrate the relationship between a high level of Sensation Seeking and illegal drug abuse. However, few studies in Colombia replicate those results. The objective is to examine the difference of Sensation Seeking personality trait and its subscales in the behaviour of drug abuse on two Colombian samples, consumers and non-consumers, measured through the Sensation Seeking Scale-V (Zuckerman & Kulhman, 1980). Methodology. 341 adult subjects, from both genders, composed the sample, half of them were consumers of illegal drugs and half of them non-consumers, assessed through Sensation Seeking Scale Version V. Results. There is a significant difference between consumers and non-consumers within the general scale and three subscales of the trait (Thrill and Adventure Seeking, Experience Seeking and Disinhibition). Discussion. Differences between the scores of consumers and non-consumers sample regarding the general trait and subtraits show the relevance of personality factors regarding substance abuse, independently than social and learning factors are influential as well. Conclusions. There is a link between Sensation Seeking and substance abuse showing the importance of the level of the trait in the multivariate phenomenon of substance dependence.